2011
DOI: 10.1080/09658211.2011.570765
|View full text |Cite
|
Sign up to set email alerts
|

Distinct and shared cognitive functions mediate event- and time-based prospective memory impairment in normal ageing

Abstract: Prospective memory (PM) is the ability to remember to perform an action at a specific point in the future. Regarded as multidimensional, PM involves several cognitive functions that are known to be impaired in normal ageing. In the present study we set out to investigate the cognitive correlates of PM impairment in normal ageing. Manipulating cognitive load, we assessed event- and time-based PM, as well as several cognitive functions, including executive functions, working memory, and retrospective episodic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
80
0
19

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 89 publications
(116 citation statements)
references
References 61 publications
16
80
0
19
Order By: Relevance
“…This suggests that, in these conditions, the TBPM task required older participants to engage more self-initiated processes (Craik 1986). More specifically, TBPM may engage more self-initiated processes than EBPM, despite the fact that, in conditions where TBPM and EBPM tasks are not made as similar as possible, the reverse pattern could be observed (see for example Gonneaud et al, 2011). Furthermore, older individuals demonstrated a higher cost of adding an intention on both accuracy and response times for the ongoing task (i.e., "natural"/"man-made" judgment) compared to young adults.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This suggests that, in these conditions, the TBPM task required older participants to engage more self-initiated processes (Craik 1986). More specifically, TBPM may engage more self-initiated processes than EBPM, despite the fact that, in conditions where TBPM and EBPM tasks are not made as similar as possible, the reverse pattern could be observed (see for example Gonneaud et al, 2011). Furthermore, older individuals demonstrated a higher cost of adding an intention on both accuracy and response times for the ongoing task (i.e., "natural"/"man-made" judgment) compared to young adults.…”
Section: Discussionmentioning
confidence: 88%
“…The greater reliance on self-initiated processes and difficulties for older adults to strategically monitor the time have been proposed to account for this greater decline in TBPM (Einstein et al 1995;Mäntylä et al 2009). Interestingly, the age-related variability in PM performance seems largely related to executive functions (Gonneaud et al 2011;Kliegel et al 2003;Martin et al 2003), which depend on the integrity of frontal areas that are also particularly sensitive to the effects of age (Kalpouzos et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…These results raise the question of the involvement of executive functions in PM functioning. There is also a debate about PM in normal aging, for whereas some studies have reported poorer PM performances for older participants (Gonneaud, Kalpouzos, Bon, et al, 2011), others have not (Uttl, 2008). For their part, Martin, Kliegel, and McDaniel (2003) claimed that "frontal/executive functioning is an important predictor for PM performance."…”
Section: Introductionmentioning
confidence: 99%
“…Proof of the paradox for time-based tasks has also been found in studies using the same sample of participants in both the laboratory tasks and the tasks situated in everyday settings (Niedźwieńska & Barzykowski, 2012;Rendell & Thomson, 1999;Schnitzspahn, Ihle, et al, 2011). This is in contrast to some that suggest that time-based tasks should be more affected by aging than eventbased tasks, because time-based tasks require more self-initiated processes (see Gonneaud et al, 2011 for a review).…”
Section: Chapter 2 Prospective Memory and Cognitive Agingmentioning
confidence: 38%
“…Research on prospective memory started late in the history of memory research (Einstein & McDaniel, 1990;McDaniel, Einstein, & Jacoby, 2008), and this ability is still regarded to be poorly understood (c.f. Gonneaud et al, 2011;Uttl, 2008). Today prospective memory has primarily been researched within laboratory-based paradigms.…”
mentioning
confidence: 99%